Plant-based vaccine candidate against Infectious bursal disease: an alternative to inactivated vaccines for breeder hens - Lucero, Maria Soledad (2019)
Infectious bursal disease (IBD) is an acute, highly contagious immunosuppressive disease that affects young birds causing important economic losses in the poultry industry worldwide. Strict hygiene management together with effective vaccination programs are the most important strategies to prevent Infectious bursal disease virus entry in poultry production facilities. Hyperimmunisation of dams with inactivated vaccines just before the laying period provides passive immunity to the progeny that protects them during the critical first few weeks after hatching before vaccination with live attenuated virus takes place. In the present study, a safe and economic plant-based vaccine candidate against IBD intended for breeder hens was evaluated. We demonstrated that the recombinant immunogen is effective as booster for previously primed hens since it increases specific antibodies against VP2 that are transmitted to the offspring with titres and decay rate similar to those achieved by inactivated vaccine. Moreover, these maternally derived antibodies have virus neutralising activity and are able to confer protection against challenge in progeny, as evidenced by absence of bursal damage and low viral titres in this organ. Taking into account the disadvantages of inactivated vaccines as well as the benefits of plants as expression systems, such as time and cost efficiency, lower risk of contamination from animal pathogens and nearly unlimited scalability, a plant-based subunit IBD vaccine represents a viable alternative in the veterinary field.